Formulation and field performance of liquid phosphate-solubilizing bacterial biofertilizer for improved growth, yield, and nutrient content of potato - Bansal, Riya; Vyas, Pratibha; Sharma, Sandeep (Frontiers in Microbiology, 2025)
In the present study, a liquid formulation(s) containing two phosphate-solubilizing Bacillus licheniformis PRPSB10 and Pseudomonas putida PRPSB38 has been developed and tested for its efficacy to improve growth, yield, and nutrient content of potato (Solanum tuberosum L.) under integrated nutrient management system. These two phosphate-solubilizing strains, isolated from potato rhizosphere showed high phosphate-solubilizing efficiency, with solubilization index of 6.1 and 5.8, respectively, on modified Pikovskaya agar. The strain PRPSB10 solubilized 659.9, 202.0, and 113.7 μg ml−1 of tricalcium phosphate, rock phosphate, and iron phosphate, respectively, while the strain PRPSB38 solubilized 457.4, 187.9, and 80.0 μg ml −1 of the same substrates, respectively, after 5 days of incubation in NBRIP broth. Among the different cell protectants tested, 0.1% carboxymethyl cellulose (CMC) was found to be the best for B. licheniformis PRPSB10 while 5 mM trehalose was best suited for P. putida PRPSB38 maintaining the cell viability ~108 CFU ml−1 up to 1 year under ambient storage conditions. Two-year field evaluations of the liquid formulation in potato variety Kufri Pukhraj with different P dosages revealed a significant improvement in plant growth, phosphorus content, tuber yield and soil fertility over the respective control treatment with an average increase of 16.2% in yield over control. Economic analysis further indicated mean net returns of ₹44,876 ha−1 and an improved benefit-cost ratio of 2.52 compared with the uninoculated control. The results indicated that the developed liquid PSB formulation exhibited excellent stability, effectively enhanced yield and phosphorus availability highlighting its potential to be used as a liquid biofertilizer for improving potato productivity and maintaining soil health.